2022
DOI: 10.48550/arxiv.2209.14202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Making statistics work: a quantum engine in the BEC-BCS crossover

Abstract: Heat engines convert thermal energy into mechanical work both in the classical and quantum regimes. However, quantum theory offers genuine nonclassical forms of energy, different from heat, which so far have not been exploited in cyclic engines to produce useful work. We here experimentally realize a novel quantum many-body engine fuelled by the energy difference between fermionic and bosonic ensembles of ultracold particles that follows from the Pauli exclusion principle. We employ a harmonically trapped supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…On the experimental side, a recently reported realization of an isothermal engine with ultra-cold atoms and tunable interactions that change the quantum statistics of the working system, provides an exciting subject for future studies [60]. Here, it is a priori unclear how a geometric framework should be constructed, since, at least in an effectively non-interacting model, the statistics of quantum particles cannot be continuously tuned between Bose-Einstein and Fermi-Dirac.…”
Section: Concluding Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the experimental side, a recently reported realization of an isothermal engine with ultra-cold atoms and tunable interactions that change the quantum statistics of the working system, provides an exciting subject for future studies [60]. Here, it is a priori unclear how a geometric framework should be constructed, since, at least in an effectively non-interacting model, the statistics of quantum particles cannot be continuously tuned between Bose-Einstein and Fermi-Dirac.…”
Section: Concluding Perspectivesmentioning
confidence: 99%
“…A promising avenue towards scaling up the power and constancy of quantum thermal machines is to replace working systems with few degrees of freedom by many-body systems capable of hosting collective effects, which may lead to uncovering new mechanisms of energy conversion . Such effects, whose thermodynamics is yet to be fully understood, include: tunable interactions between particles, which can be used for work-extraction [44][45][46]; super-radiance and broken time-translation symmetry, which emerge in multi-level systems coupled to a thermal bath via collective observables [47][48][49][50][51][52]; quantum phase transitions [53][54][55][56] or quantum statistics, which provides a means of controlling an effective pressure that has no classical counterpart [57][58][59][60][61]. Thermodynamic geometry offers a powerful tool to analyse these phenomena from a unifying perspective and thus a potential avenue towards a universal framework describing how many-body effects can alter the performance of quantum thermal machines.…”
Section: Introductionmentioning
confidence: 99%
“…While recent years have seen the experimental implementation of some quantum thermodynamic cycles [ 11 , 13 , 31 , 32 ], these devices serve primarily as proof-of-concept prototypes rather than a practical means of extracting useful energy in the form of work. This is since coupling a quantum thermal machine to another device to extract and use the work is a complex and challenging task within the frameworks in which these quantum engines have been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach to the first challenge is to replace working media with few degrees of freedom, such as single spins, with many-body systems, where collective effects can arise from the co-action of large numbers of constituents [13]. Recent theoretical and experimental studies have shown that the power of thermal devices can be significantly enhanced by exploiting, for example, many-body coherence in non-interacting systems, which can give rise to super-radiance and related phenomena [14][15][16][17][18][19][20][21][22][23][24], or interactions and quantum many-body statistics in ultra-cold atomic systems [25][26][27][28][29][30][31][32][33][34][35]. Strongly interacting Rydberg atoms and ions provide another, yet relatively unexplored, platform to implement quantum thermal machines with many degrees of freedom [39].…”
mentioning
confidence: 99%